ChemInform Abstract: Aryl(trifluoroethyl)iodonium Triflimide and Nitrile Solvent Systems: A Combination for the Stereoselective Synthesis of Armed 1, 2‐trans‐β‐Glycosides at Noncryogenic Temperatures. Issue 19 (April 2016) - Chu, An‐Hsiang Adam; Minciunescu, Andrei; Bennett, Clay S.
Abstract: The optimal mixed solvent system is dichloromethane/acetonitrile/isobutyronitrile/pivalonitrile (6:1:1:1).